Determination of pyrimidine 5'-nucleotidase (P5N) activity in whole blood as an index of lead exposure. Issue 6 (June 1988) - Sakai, T; Araki, T; Ushio, K
Abstract : A simple method for determining pyrimidine 5'-nucleotidase (P5N) activity in whole blood has been developed, inhibiting the plasma activity for UMP-hydrolysis by concanavalin (Con A). Con A specifically inhibits the activity of plasma 5'-nucleotidase (5N) but does not affect erythrocyte P5N activity. The anticoagulant EDTA partially inhibits 5N activity but slightly activates P5N. P5N activity determined by the present method with heparinised blood and Con A was comparable with that by the method reported previously and correlated well with blood lead concentrations. The mean value and SD for P5N activity in normal subjects (n = 72) not exposed to lead are 16.2 and 2.5 mumole/h/g Hb, respectively. The present method can eliminate not only the isolation step of RBC but also Hb determination, the activity being expressed as mumole/h/l blood or RBC. Thus the procedures are so simplified that the assay may be used as a routine test for mass screening of lead exposure.